2005
DOI: 10.1210/jc.2004-1254
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous and Heterozygous Expression of a Novel Insulin-Like Growth Factor-I Mutation

Abstract: IGF-I is a key factor in intrauterine development and postnatal growth and metabolism. The secretion of IGF-I in utero is not dependent on GH, whereas in childhood and adult life, IGF-I secretion seems to be mainly controlled by GH, as revealed from studies on patients with GHRH receptor and GH receptor mutations. In a 55-yr-old male, the first child of consanguineous parents, presenting with severe intrauterine and postnatal growth retardation, microcephaly, and sensorineural deafness, we found a homozygous G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
217
0
12

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(249 citation statements)
references
References 58 publications
10
217
0
12
Order By: Relevance
“…(1)(2)(3)11) A role of IGF-1 in bone metabolism is supported by the fact that patients with IGF deficiency as a result of IGF1 gene deletion or inactivating mutation display osteopenia. (12)(13)(14) The association between serum IGF-1 and BMD has been evaluated in several cohorts but with conflicting results. (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) A positive association has been reported in some studies, (15,17,(20)(21)(22)(23)25,26) whereas no association has been found in other studies.…”
Section: Introductionmentioning
confidence: 99%
“…(1)(2)(3)11) A role of IGF-1 in bone metabolism is supported by the fact that patients with IGF deficiency as a result of IGF1 gene deletion or inactivating mutation display osteopenia. (12)(13)(14) The association between serum IGF-1 and BMD has been evaluated in several cohorts but with conflicting results. (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) A positive association has been reported in some studies, (15,17,(20)(21)(22)(23)25,26) whereas no association has been found in other studies.…”
Section: Introductionmentioning
confidence: 99%
“…5 Clinical studies have shown that human patients with lossof-function mutations in either IGF-1 or the IGF1R suffer severe intrauterine growth restriction and poor postnatal growth, as well as microcephaly, deafness and mental retardation. [6][7][8][9][10] Mouse genetic studies further established the causational importance of IGF1R signaling in fetal growth and development. IGF1R null mutant mice exhibited severe growth retardation at birth (45% of wild-type littermates) and died shortly after birth from respiratory failure.…”
mentioning
confidence: 98%
“…These were located in exons 2, 7, 11 and 16, respectively. [1][2][3][4][5] Short stature was present in all cases, mild motor and/or speech developmental delay in 4/9 cases and mild intellectual disabilitywith a Wechsler intelligence quotient of 60 -in one case of a patient with a missense mutation in exon 11. This missense mutation was detected in a girl whose mother, a carrier of the same mutation, did not show any neuropsychiatric abnormalities and had normal intelligence.…”
Section: Discussionmentioning
confidence: 94%
“…They were associated with various constellations of clinical findings, including growth deficit, microcephaly, developmental delay, mild facial dysmorphisms and skeletal deformations in affected individuals. [1][2][3][4][5][6][7][8][9][10][11] Usually intrauterine or postnatal growth deficits were moderate to severe in these patients. Notably, cognitive dysfunction of the reported individuals was either moderate, mild or absent.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation